2019
DOI: 10.3390/informatics6040043
|View full text |Cite
|
Sign up to set email alerts
|

Educational Robotics in Primary School: Measuring the Development of Computational Thinking Skills with the Bebras Tasks

Abstract: Research has shown that educational robotics can be an effective tool to increase students’ acquisition of knowledge in the subjects of science, technology, engineering, and mathematics and promote, at the same time, a progression in the development of computational thinking (CT) skills in K–12 (kindergarten to 12th grade) education. Within this research field, the present study first sought to assess the effect of a robotics laboratory on the acquisition of CT-related skills in primary school children. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 30 publications
1
30
0
6
Order By: Relevance
“…In addition, it can be stated that students' hand skills increased, they rendered the course interesting by enabling the use of rich and accessible material and the students were able to learn having fun and thus increased their academic achievement (Ozdogru, 2013;Vollstedt, 2005). On the other hand, there are some studies indicating that there is no significant increase in terms of the academic achievement of educational robotic applications or where there are no significant differences when compared with other studies (Cakir, 2019;Chiazzese, Arrigo, Chifari, Lonati & Tosto, 2019;Jomento-Cruz, 2010;Li, Huang, Jiang & Chang, 2016). The reason for obtaining different results in these studies in the literature may be the application of courses in different ways, differences in the activities used during the course and the teacher's management of the process in a different way.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, it can be stated that students' hand skills increased, they rendered the course interesting by enabling the use of rich and accessible material and the students were able to learn having fun and thus increased their academic achievement (Ozdogru, 2013;Vollstedt, 2005). On the other hand, there are some studies indicating that there is no significant increase in terms of the academic achievement of educational robotic applications or where there are no significant differences when compared with other studies (Cakir, 2019;Chiazzese, Arrigo, Chifari, Lonati & Tosto, 2019;Jomento-Cruz, 2010;Li, Huang, Jiang & Chang, 2016). The reason for obtaining different results in these studies in the literature may be the application of courses in different ways, differences in the activities used during the course and the teacher's management of the process in a different way.…”
Section: Discussionmentioning
confidence: 94%
“…Fink (2008) said that comparing DNA sequences and translating the DNA to protein needs the skill of pattern recognition. Pattern recognition consists of recognizing specific repeated situations and generalizing them (Chiazzese et al,. 2019).…”
Section: Discussionmentioning
confidence: 99%
“…2020) who developed a module for computer engineering students in university to improve CTs. Chiazzese et al (2019) assessed CTs of students in K-12 education after learning programming about robotics. The result showed that programming robotics has a positive impact on students' learning of CTs.…”
Section: The Effect Of Bioinformatics Module On Molecular Genetics Co...mentioning
confidence: 99%
See 1 more Smart Citation
“…Computer Science Unplugged (CS Unplugged [1]) and Bebras tasks [4,6] are a widely used collections of activities to introduce both children and adults to ideas and concepts from computer science, without having to use a digital device. With the variety of material appearing, the term "Unplugged" is currently used for computer science teaching activities that do not involve programming and the term refers to a general pedagogical approach.…”
Section: Introductionmentioning
confidence: 99%